Development of a Nasi Kotak E-Book to Support Learning in Manajemen Usaha Boga - Titis Budi Rahayu (Universitas Negeri Semarang, 2025)
This study aimed to (1) develop an e-book on Nasi Kotak materials, (2) evaluate its feasibility, and (3) assess student satisfaction with its use. The research employed a Research and Development (R&D) approach using the 4 D model, which includes the stages of Define, Design, Develop, and Disseminate. Data were collected through needs analysis observations, feasibility assessment questionnaires, and student satisfaction surveys. The e-book development process involved identifying learning needs, designing content structure and layout, producing and validating the e-book through expert review, and distributing it via the LMS platform. The results indicated that the e-book met the required standards of feasibility with average score 3.33, and received highly positive feedback from students with average score 3.38, demonstrating its effectiveness as an engaging and accessible learning resource.